Employee attendance system using Flutter / Muhamad Faiz Akmal Mohamad Noor and Alif Faisal Ibrahim - Mohamad Noor, Muhamad Faiz Akmal; Ibrahim, Alif Faisal (College of Computing, Informatics and Media, UiTM Perlis, 2023)
The proposed mobile application, developed using the Flutter framework and Dart programming language, is designed to replace the traditional, manual process of recording attendance through paper. The application will not only record the attendance of the employees but also will be recording the location from where the employee clock in or out. The development process follows the Waterfall method of the System Development Life Cycle. The primary objective of this project is to design and develop an attendance application that improves the accuracy and reliability of attendance records while also increasing the convenience and efficiency of the attendance recording process for employees. The functionality and usability of the application will be thoroughly tested to ensure it meets the needs of the users.